(untitled) (Journal of Informatics Education and Research, 2024)
The study aims to explore the factors that affect the use of Over-the-top (OTT) streaming services on Connected TVs. Customers have started using OTT streaming along with DTH (Direct to Home) and Cable Network. Connected TVs have become an essential part of Indian households due to their affordability and improved internet accessibility. The emergence of OTT streaming platforms has contributed to the increased market presence of connected TVs in India. Additionally, there has been significant development in internet infrastructure, such as broadband connectivity and the transition to 5G mobile technology, which has enabled connected TV users to access a variety of streaming content worldwide. The study also focuses on the adoption and usage of OTT streaming on Connected TV/Smart TVs, given the rising popularity of OTT content.